Impact of Pyramid Meditation On Anxiety and Stress Among Youth: Life Sciences - Shukla, Vivek; Kumar, Nitendra; Kant Pal, Surya; Tiwari, Sadhana; Agarwal, priyanka (International Journal of Life Science and Pharma Research, 2023)
A pyramid is a polyhedron with any base and three or more triangular faces that meet at a point called an apex or a pyramid is a three-dimensional shape with triangular sides. The pyramidal structure is a storehouse of energy. The pyramid is said to have the power to heal your chakras and align your mind. There are three main examples of a pyramid in our real life, are perfume bottles, tents in military camps and the roof of a house. Pyramid meditation is designed to increase vision and for other many benefits such as strengthening eye muscles, improving hearing, lowering blood pressure, relieving arthritis symptoms and treating insomnia. It can also help improve memory and cognitive function, as well as healthy skin and hormonal balance. Now a day, anxiety and stress are common problem among the youth. This study talks about the effect of Pyramid meditation on the variables of stress and anxiety among adults. There are 200 participants participated in this survey out of which 100 were meditation practitioners and other 100 participants were non-practitioners. To assess the level of anxiety, Beck Anxiety Inventory and for stress, perceived stress scale by Cohen were administered. The data was processed using statistical computations like mean, median, mode and standard deviation. The results reflected a significant difference between the scores of meditation practitioners and non-practitioner youths. It was found that those who practice pyramid meditation had considerably low level of anxiety and stress than that of those who do not meditate.